An overview of current treatment strategies for β-thalassemia. (July 2014) - Cappellini, Maria Domenica; Viprakasit, Vip; Taher, Ali T
<x xml:space="preserve">Abstract</x> Introduction: At least 40, 000 people per year worldwide are born with β-thalassemia. Patients with β-thalassemia major are reliant on regular red blood cell transfusions for survival from a young age. For those with β-thalassemia intermedia or hemoglobin (Hb) E/β-thalassemia, symptoms range from mild clinical presentation to a more severe phenotype and patients are not necessarily transfusion-dependent. Areas covered: Here, β-thalassemia treatment strategies including transfusion, splenectomy, fetal hemoglobin induction, hematopoietic stem-cell transplantation, in addition to potential future treatment options, are reviewed. Approaches for the monitoring and management of complications are also described. Expert opinion: The most important advances in the treatment of transfusion-dependent β-thalassemia major patients since the advent of iron chelation therapy are the introduction of oral iron chelators in addition to technologies for the direct measurement of iron in organs. For non-transfusion-dependent patients with β-thalassemia intermedia or HbE/β-thalassemia, recent studies have highlighted the significance of iron overload-related complications and the increase in incidence with advancing age, prompting the development of much-needed clinical treatment guidelines. Future research should focus on improving the treatment of β-thalassemia major patients to further extend survival and quality of life, and continued identification of β-thalassemia intermedia or HbE/β-thalassemia patients who may benefit from transfusion and iron chelation therapy.